The effects of parenting stress on father-child brain synchrony - Ang, Anais Xin Hui (Nanyang Technological University, 2020)
Synchrony between a parent and child sets the foundation for the parent-child bond and has lasting effects on a child’s developmental outcomes. Greater synchrony is generally found to be associated with more positive parent-child relationships. However, when the stresses of parenthood extend beyond a parent’s coping resources, it can reduce parent-child synchrony, in turn negatively affecting their relationship. A recent study by Azhari et al. (2019) found that greater maternal stress was associated with reduced brain synchrony in the medial left cluster of the prefrontal cortex (PFC), a region implicated in mentalization processes. As mothers and fathers experience parenting stress differently, this study sought to find out how parenting stress in fathers affects brain synchrony between fathers and their children using similar experimental methodology. The fNIRS hyper-scanning technique was used to measure brain activity in the PFC in 29 father-child dyads while they watched three 1-minute animation clips together. Parenting stress was measured using the Parenting Stress Index – Short Form (PSI-SF) questionnaire. Results show that fathers who were more stressed due to perceived dysfunction in parent-child interactions showed higher synchrony in the medial rostral Brodmann Area 10 (BA10), a brain region is associated with stimulus-oriented attending. This suggests father-child dyads with more dysfunctional interactions may have an inclination towards focusing on stimuli during a joint activity rather than being attuned to each other’s emotional states. Future research could further explore how parenting stress affects the father-child relationship.